The role of Indonesian regulators on the effectiveness of ESG implementation in improving firms' non-financial performance - Ni Putu Gita Rahmaniati; Erni Ekawati (Cogent Business & Management, 2024)
Recent studies have addressed the impact of Environment, Social, and Governance responsibility on corporate financial performance and value, but often ignore its impact on non-financial performance. Whereas the ultimate goal of ESG responsibilities is non-financial matters, that is, to incorporate socially acceptable norms into business activities to reach sustainable goals for society. Employing an unbalance panel data model for listed companies in Indonesian Stock Exchange from 2016 to 2022, this study provides empirical evidence on the indirect impact of ESG implementation on firms' non-financial performance. Consistent with the stakeholder theory, this study found a positive impact of ESG implementation on firm values. The predictability of ESG performance in future financial performance is in line with the resource-based views. ESG-related financial performance has a positive impact on non-financial performance. Firms are willing to increase their commitment to ESG activities if these activities can primarily improve their financial performance. The regulatory policy with dual materiality characteristic is effective in mitigating the mere financial motives of ESG implementation to the more substantive outcomes on ESG-related issues. The effective law enforcement is able to encourage the companies not only to symbolically implement the ESG but to go beyond the legitimate substantive strategic implementation.
Keywords: 650; ESG implementation; firm value; ESG-related financial performance; non-financial performance; law enforcement